Tinjauan Hukum Islam terhadap Keputusan Istri yang Melakukan Program Keluarga Berencana (KB) Tanpa Izin dari Suami - Agung Wicaksono; Lilik Andar Yuni (Bulletin of Community Engagement, 2024)
The Family Planning (FP) program is an effort to control the number and spacing of births to maintain family welfare. In the Islamic perspective, contraception has long been acknowledged through the practice of 'azl, which is permitted as long as it is based on mutual agreement between husband and wife. However, debates arise when a wife decides to use contraception without her husband's consent, particularly when her health is a primary consideration. This article aims to analyze the Islamic legal perspective on a wife's decision to use FP without her husband's approval, employing a normative approach. The findings reveal that Islam provides flexibility for women to protect their health, even without their husband's consent, if the action is intended to safeguard the wife's well-being and life. The principles of maqashid shariah and the legal maxim la dharara wa la dhirara provide a legal basis for this decision. While consultation between spouses is encouraged, the wife's health remains a priority in Islam.